The dead play on [large type] - Graham, Heather (Graham, Heather. Cafferty & Quinn novel, 2015)
Musicians are being murdered in New Orleans. But Arnie Watson apparently died by his own hand. When Tyler Anderson plays the saxophone he inherited from Arnie, a soldier and musician who died soon after his return, he believes he sees visions of his friend's life--and death. He becomes convinced Arnie was murdered and that the instrument had something to do with whatever happened, and with whatever's happening all over the city. Tyler knows his theory sounds crazy to the police, so he approaches Danni Cafferty, hoping she and Michael Quinn will find out what the cops couldn't. Or wouldn't. After all, Cafferty and Quinn have become famous for solving unusual crimes.